IMPLEMENTASI TOLERANSI BERAGAMA: INTERAKSI SOSIAL ANTARA UMAT ISLAM KOTA BIMA DAN NON MUSLIM NTT (STUDI KASUS DI PADOLO KOTA BIMA) - Farijal Zukril Lita; Muhammad Irfan; Junaidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of tolerance and patterns of religious social interaction between the Muslim majority and non-Muslim minority (from NTT) in the Padolo neighborhood, Paruga subdistrict, Bima city. The study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. The results of the study indicate that despite challenges such as limited access to worship infrastructure for minorities and the existence of stereotypes, interfaith social relations in Padolo are very harmonious and collaborative. The main driving factors lie in the practice of local wisdom values such as mutual respect, active tolerance, and a spirit of mutual cooperation (Mbolo Weki), which are manifested in joint activities such as holiday celebrations, community service, and deliberations. Minority groups developed adaptive strategies such as rotating worship services in homes to overcome technical constraints. The conclusion of this study is that harmony in Padolo is not a problem-free situation, but rather the result of the community's ability to constructively manage differences through a local wisdom-based approach and ongoing dialogue. Diversity actually functions as a social glue that transforms differences into a source of strength for creating sustainable peace. These findings can serve as an example of best practices for other regions in managing religious diversity.